Sketching user experiences : the workbook - Greenberg, Saul, 1954- (Morgan Kaufmann, 2012)
In Sketching User Experiences: The Workbook, you will learn, through step-by-step instructions and exercises, various sketching methods that will let you express your design ideas about user experiences across time. Collectively, these methods will be your sketching repertoire: a toolkit where you can choose the method most appropriate for developing your ideas, which will help you cultivate a culture of experience-based design and critique in your workplace. Features standalone modules detailing methods and exercises for practitioners who want to learn and develop their sketching skills Extr.